2015
DOI: 10.1172/jci80280
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Krüppel-like factor 6 cripples podocyte mitochondrial function

Abstract: C o m m e n t a r y 9 6 8

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
(27 reference statements)
2
5
0
Order By: Relevance
“…As a prototypical pro‐oxidant, ADR is known to cause podocyte loss by inducing oxidative stress and podocyte mitochondrial dysfunction, ensued by podocyte loss and podocytopenia . In concordance with this, fluorescence immunohistochemistry (Figure A) and immunoblot analysis of isolated glomeruli for WT1 (Figure B) indicated that ADR injury resulted in striking podocytopenia in Ctrl mice on day 6, associated with evident mitochondria damage in podocytes, characterized by a decreased number of mitochondria, mitochondrial swelling and fragmentation, destruction of the inner mitochondrial membrane, and disruption of mitochondrial cristae on electron microscopy (Figure C).…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…As a prototypical pro‐oxidant, ADR is known to cause podocyte loss by inducing oxidative stress and podocyte mitochondrial dysfunction, ensued by podocyte loss and podocytopenia . In concordance with this, fluorescence immunohistochemistry (Figure A) and immunoblot analysis of isolated glomeruli for WT1 (Figure B) indicated that ADR injury resulted in striking podocytopenia in Ctrl mice on day 6, associated with evident mitochondria damage in podocytes, characterized by a decreased number of mitochondria, mitochondrial swelling and fragmentation, destruction of the inner mitochondrial membrane, and disruption of mitochondrial cristae on electron microscopy (Figure C).…”
Section: Resultssupporting
confidence: 59%
“…As a prototypical pro-oxidant, ADR is known to cause podocyte loss by inducing oxidative stress and podocyte mitochondrial dysfunction, ensued by podocyte loss and podocytopenia [50]. In concordance with this, fluorescence immunohistochemistry ( Figure 6A) and immunoblot analysis of isolated glomeruli for WT1 ( Figure 6B) indicated that ADR injury resulted in Figure 5.…”
Section: Gsk3β Knockout Mitigates the Adr-elicited Mitochondria Dysfusupporting
confidence: 53%
“…Along with others, we have reported an essential role of Krüppel-like factors (KLFs) in glomerular biology (1618). KLFs are a subtype of zinc-finger transcriptional factors that are involved in several fundamental cellular processes (18,19).…”
Section: Introductionmentioning
confidence: 59%
“…Some studies reported that mitochondrial dysfunction is involved in podocyte injury (16,17). The results of our previous study revealed that PKA signaling prevented PAN-induced mitochondrial fission and apoptosis in podocytes, suggesting that mitochondrial function may be important in this process (12).…”
mentioning
confidence: 87%